2021
DOI: 10.1002/ece3.8120
|View full text |Cite
|
Sign up to set email alerts
|

Warm‐night temperature alters paternal allocation strategy in a North temperate‐zone butterfly

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…Whitney and Johnson (2005) showed that increasing the nighttime temperature increased the intrinsic rate of growth in Pieris rapae [48]. The effects of nighttime temperatures on the adult lifespan of the Finnish Glanville fritillary butterfly (Melitaea cinxia) [49] were similar with this study. The larval and pupal survival was only significantly affected by the highest daytime temperature.…”
Section: Discussionsupporting
confidence: 84%
“…Whitney and Johnson (2005) showed that increasing the nighttime temperature increased the intrinsic rate of growth in Pieris rapae [48]. The effects of nighttime temperatures on the adult lifespan of the Finnish Glanville fritillary butterfly (Melitaea cinxia) [49] were similar with this study. The larval and pupal survival was only significantly affected by the highest daytime temperature.…”
Section: Discussionsupporting
confidence: 84%
“…According to recent reports, temperatures turn out to rise at a faster speed at night than daytime. Experiments have been done in the study of Elena Rosa et tal [4]. In the experiment, the responses of Melitaea cinxia towards increasing temperature during night times are studied.…”
Section: Oviposition Climate Change Influences Butterflies From a Var...mentioning
confidence: 99%
“…Thus, it is important to account for food consumption when determining plasticity in life-history strategies, which may be one of the animals' key defences against ongoing environmental change [20][21][22]. Warming influences resource allocation patterns across animal taxa [23][24][25]-yet, the combined and potentially opposing effects of heatwave exposure and predation risk on life-history strategy are poorly understood.…”
Section: Introductionmentioning
confidence: 99%